2022
DOI: 10.1108/jfbm-03-2022-0044
|View full text |Cite
|
Sign up to set email alerts
|

Business process innovations in family firms: evidence from Serbia

Abstract: PurposeThis paper aims to explore the innovation performance of Serbian family firms, the differences in the innovation performance between family and non-family firms as well as different family firms, and the relationship between business process innovation and customer satisfaction among family firms.Design/methodology/approachThe sample consists of 207 valid responses from young Serbian companies from various industries founded in 2015 that published their financial statements in 2017. The statistical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
2
3
0
Order By: Relevance
“…However, in our sample, family firms could not rely on their innovation capabilities to reach higher performance, thus leading to the conclusion that they seem only as innovative as non-family businesses, no better or less. This is similar to the findings of Paunović et al (2023) who also found that family and non-family businesses are equally committed to introducing innovations in their business processes and to Csákné Filep et al (2023) who found no difference between family and non-family firms regarding their innovation performance in their 2017 and 2022 samples.…”
Section: Iv5 Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, in our sample, family firms could not rely on their innovation capabilities to reach higher performance, thus leading to the conclusion that they seem only as innovative as non-family businesses, no better or less. This is similar to the findings of Paunović et al (2023) who also found that family and non-family businesses are equally committed to introducing innovations in their business processes and to Csákné Filep et al (2023) who found no difference between family and non-family firms regarding their innovation performance in their 2017 and 2022 samples.…”
Section: Iv5 Discussionsupporting
confidence: 87%
“…However, in our sample, family firms could not rely on their innovation capabilities to achieve higher competitiveness, and we conclude that domestic medium-sized family firms do not outperform their non-family competitors in terms of innovation performance. Our results are similar to the findings of Paunović, Ružičić & Moravčević (2023), who also found that family and non-family firms are equally committed to introducing innovations in their business processes and to the research on a domestic sample (Németh & Dőry, 2019), where they also found no evidence of significant differences between family and non-family firms in terms of innovation orientation. The research also confirms our claim that family firms have failed to take advantage of their innovation capabilities, as there is a demonstrable link between the use of professional management tools and systems and innovation performance.…”
Section: Contributions Of Chapter IV a Quantitative Study On Family A...supporting
confidence: 90%
“…In the same context, while some research indicates that family firms are willing to execute innovation in business processes like production and distribution operations [44,45], other studies show that family firms invest less in research and development and that introducing change in processes and products is due to their flexibility [46]. Regarding the use of information technology and data organization in family SMEs, Dutot et al [47] showed that FSMEs do not have mature, adequate management and use of ICT (information and communication technology).…”
Section: Referencesmentioning
confidence: 99%
“…These issues are considered further by Paunović et al (2022) in a study of family and non-family firms in Serbia, a country where businesses have been slow to exploit their scope for innovation. The need to implement innovative solution is increasing as the shift from traditional to digital business accelerates.…”
Section: Serbian Study and Indicationsmentioning
confidence: 99%